Legal Protection For Notaries Against False Information Given By Participants In The Drafting of Authentic Deeds - Octavia, Jane Maria; Silviana, Ana (Faculty of Law, Universitas Pattimura, 2024)
Introduction: A problem that often occurs in connection with the implementation of the duties of a Notary is if there is a Notarial deed that is faulted by the parties, especially if the parties come to the Notary with false information or fake evidence.Purposes of the Research: This research aims to analyze the validity of a notary's statement which is based on evidence that is declared to be fake and legal protection for notaries for fake statements.Methods of the Research: This research uses normative legal research methods by looking for solutions and legal issues that arise, which will be achieved and then provide predictions. Legal approach and conceptual approach, with primary and secondary legal materials.Results of the Research: Based on Supreme Court Decision Number 702/J/Sip/1973 dated September 5 1973, the Notary who recorded what was shown and conveyed by the person facing, there is no obligation for the notary to investigate materially. In this way, the Notary is not asked to be held responsible for losses incurred because the parties provided false information.